Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Melalui Kinerja Keuangan Perusahaan BUMN Yang Terdaftar Di Bursa Efek Indonesia - Patodo, Geifrila Elizabeth A; Susilowati, Dwi; Moorcy, Nadi Hermadi (Jurnal Edueco, 2025)
Geifrila Elizabeth A. Patodo (2024). The Effect of Good Corporate Governance on Firm Value Through the Financial Performance of State-Owned Companies Listed on the Indonesia Stock Exchange. Advisor: Mrs. Dwi Susilowati and Mr. Nadi Hernadi Moorcy. The purpose of this study was to determine the effect of the Independent Board of Commissioners, Managerial Ownership, and Audit Committee on Price to Book Value and Return On Asset. This study also aims to determine the effect of Return On Asset in mediating the Independent Board of Commissioners, Managerial Ownership, and Audit Committee on Price to Book Value. The data used comes from the annual financial statements of state-owned companies listed on the IDX for the 2020-2023 period. The data analysis method using SmartPLS 3 software shows that the Board of Independent Commissioners and Managerial Ownership have no effect on PBV, but the audit committee has an influence on PBV. The Board of Independent Commissioners has no effect on ROA, Managerial Ownership and the Audit Committee have an influence on ROA. Then ROA has no effect on PBV and cannot mediate the variables X1, X2, and X3 on Y. Keywords: Independent Board of Commissioners, Managerial Ownership, Audit Committee, Price to Book Value, Return On Asset